RAB23 regulates musculoskeletal development and patterning - Hasan, Md. Rakibul; Koskenranta, Anna; Alakurtti, Kirsi; Takatalo, Maarit; Rice, David P. (Frontiers in Cell and Developmental Biology, 2023)
RAB23 is a small GTPase which functions at the plasma membrane to regulate growth factor signaling. Mutations in RAB23 cause Carpenter syndrome; a condition that affects normal organogenesis and patterning. In this study, we investigate the role of RAB23 in musculoskeletal development and show that it is required for patella bone formation and for the maintenance of tendon progenitors. The patella is the largest sesamoid bone in mammals and plays a critical role during movement by providing structural and mechanical support for the knee. Rab23-/- mice fail to form a patella and normal knee joint. The patella is formed from SOX9 and scleraxis (Scx) double-positive chondroprogenitor cells. We show that RAB23 is required for the specification of SOX9 and scleraxis double positive patella chondroprogenitors during the formation of patella anlagen and subsequent establishment of patellofemoral joint. We find that scleraxis and SOX9 expression are disrupted in Rab23-/- mice, and as a result development of the quadriceps tendons, cruciate ligaments, patella tendons and entheses are either abnormal or lost. TGFβ-BMP signaling is known to regulate patella initiation, patella progenitor differentiation and growth. We find that the expression of TGFβR2, BMPR1, BMP4 and pSmad are barely detectable in the future patella site, in the rudimentary tendons and ligaments around the patellofemoral joint in Rab23-/- mice. Also, we show that GLI1, SOX9 and scleraxis which regulate entheses establishment and maturation are weakly expressed in Rab23-/- mice. Further analysis of the skeletal phenotype of Rab23-/- mice showed a close resemblance to that of Tgfβ2-/- mice highlighting a possible role for RAB23 in regulating TGFβ superfamily signaling.